Deliberation across deeply divided societies : transformative moments - Steiner, Jürg; Jaramillo, Maria Clara; Maia, Rousiley; Mameli, Simona (Cambridge University Press, 2017)
This analysis of deliberative transformative moments gives deliberative research a dynamic aspect, opening practical applications in deeply divided societies.